Gene discovery in an invasive tephritid model pest species, the Mediterranean fruit fly, Ceratitis capitata - Gomulski, Ludvik M (BioMed Central, 2008)
BACKGROUND: The medfly, Ceratitis capitata, is a highly invasive agricultural pest that has become a model insect for the development of biological control programs. Despite research into the behavior and classical and population genetics of this organism, the quantity of sequence data available is limited. We have utilized an expressed sequence tag (EST) approach to obtain detailed information on transcriptome signatures that relate to a variety of physiological systems in the medfly; this information emphasizes on reproduction, sex determination, and chemosensory perception, since the study was based on normalized cDNA libraries from embryos and adult heads. RESULTS: A total of 21,253 high-quality ESTs were obtained from the embryo and head libraries. Clustering analyses performed separately for each library resulted in 5201 embryo and 6684 head transcripts. Considering an estimated 19% overlap in the transcriptomes of the two libraries, they represent about 9614 unique transcripts involved in a wide range of biological processes and molecular functions. Of particular interest are the sequences that share homology with Drosophila genes involved in sex determination, olfaction, and reproductive behavior. The medfly transformer2 (tra2) homolog was identified among the embryonic sequences, and its genomic organization and expression were characterized. CONCLUSION: The sequences obtained in this study represent the first major dataset of expressed genes in a tephritid species of agricultural importance. This resource provides essential information to support the investigation of numerous questions regarding the biology of the medfly and other related species and also constitutes an invaluable tool for the annotation of complete genome sequences. Our study has revealed intriguing findings regarding the transcript regulation of tra2 and other sex determination genes, as well as insights into the comparative genomics of genes implicated in chemosensory reception and reproduction.